Ciudades escritas. Crónicas desde EEUU - Pérez Llahí, Marcos Adrián (Imagofagia, 2021)
Sobre Soberón, Fabián. Ciudades escritas. Crónicas desde EEUU, Villa María: Eduvim, 2015, 82 pp., ISBN: 978-987-699-144-5.